Analysis of the profile of recyclable waste pickers in the municipality of Laranjeiras do Sul, Paraná - Rode, Grasieli de Fátima (2021)
This study aimed to analyze the profile of recyclable waste pickers in the municipality of Laranjeiras do Sul, Paraná, Brazil, and to relate to Amartya Sen’s deprivation of liberty theory. The identification of the profile of recyclable waste pickers occurred from a survey of primary data through interviews. The research is characterized as a case study and was constructed from a bibliographical survey, using descriptive and explanatory methods, with a quantitative and qualitative approach. The results showed that the waste pickers coexist with numerous deprivations of freedoms, such as low schooling and income; advanced age without access to social security; lack of basic documents for fundamental rights access; deprivations that limit the reach of a minimum level of living conditions.